Aerobic exercise training as a potential source of natural antibodies protective against human immunodeficiency virus-1 - Veljkovic, M.; Dopsaj, V.; Stringer, W. W.; Sakarellos-Daitsiotis, M.; Zevgiti, S.; Veljkovic, V.; Glisic, S.; Dopsaj, M. (Scandinavian journal of medicine & science in sports, 2010)
Despite the effectiveness of HAART in controlling HIV‐1 replication, the emergence of drug‐resistant viruses in infected patients and the severe side effects caused by the currently used drug regimens and the lack of an effective vaccine necessitate the continued search for new therapeutic strategies for prevention and therapy of HIV disease. Previously we reported that natural autoantibodies, recognizing peptide FTDNAKTI (peptide NTM1) derived from the C2 domain of HIV‐1 gp120, contribute to the control of HIV disease. Here we demonstrated that sera from well‐trained athletic (HIV‐negative) subjects showed high reactivity with peptide NTM1. This result confirms that aerobic exercise training stimulates production of natural autoantibodies, which recognize peptide NTM1. Bioinformatics analysis indicates that these natural autoantibodies could slow down disease progression by blocking the superantigenic site on HIV‐1 gp120. The results suggest that aerobic exercise training may be a promising non‐toxic and inexpensive adjunctive anti‐HIV therapy.